HAMBATAN BELAJAR MATEMATIKA: STUDI KASUS DI KELAS VIII SUATU SEKOLAH DI SEMARANG [BARRIERS TO LEARNING MATHEMATICS: A CASE STUDY OF GRADE 8 STUDENTS AT A SCHOOL IN SEMARANG] - Fernandes, Luis; Winardi, Yonathan; Appulembang, Oce Datu (Universitas Pelita Harapan, 2019)
Christian education aims to enable students to take part in serving God and others both now and forever. The barriers to learning mathematics make it difficult for students to achieve the goals of Christian education. In some cases, students are found to have barriers to learning mathematics. Based on this problem, the researchers wanted to know the types of barriers to learning mathematics, the causes, and the responses of teachers, schools, and students to these barriers. This study used the case study method of a qualitative approach and the subjects were grade 8 students. The data collection techniques used were interviews for mathematics teachers and principals as well as open-ended questionnaires for students. The results revealed that there were barriers to learning mathematics that can be categorized into internal and external factors including a lack of learning willingness on the part of the students, inappropriate views of mathematics, uncontrolled classroom conditions, and the contagion of the environment. The responses given by teachers, schools, and students about mathematics learning barriers include reviewing, giving additional lessons, and relearning either individually or through others. Suggestions for teachers and principals are to organize workshops related to mathematics learning barriers and improving teaching quality.BAHASA INDONESIA ABSTRAK: Pendidikan Kristen bertujuan membuat para siswa dapat mengambil bagian pelayanan kepada Tuhan dan sesama baik sekarang maupun selamanya. Dengan adanya hambatan belajar matematika menyebabkan siswa sulit mencapai tujuan dari pendidikan Kristen. Dalam beberapa kesempatan, sering ditemukan siswa yang memiliki hambatan belajar matematika. Untuk itu peneliti ingin mengetahui macam hambatan belajar matematika, penyebabnya, serta respon guru, sekolah dan siswa terkait dengan hambatan belajar matematika. Penelitian ini menggunakan pendekatan kualitatif jenis studi kasus dengan subjek siswa kelas VIII. Teknik pengumpulan data yang digunakan yaitu wawancara terhadap guru matematika dan kepala sekolah serta kuisioner terbuka bagi siswa. Hasil penelitian menunjukkan bahwa terdapat hambatan belajar matematika yang dapat dikategorikan ke dalam faktor internal dan eksternal, diantaranya siswa malas belajar, pandangan yang kurang tepat terhadap pelajaran matematika, kondisi kelas yang tidak kondusif dan pengaruh yang buruk dari lingkungan sekitar. Respon yang diberikan guru, sekolah dan siswa terhadap hambatan belajar matematika diantaranya menjelaskan kembali materi, memberikan pelajaran tambahan dan belajar kembali secara individu maupun melalui orang lain. Saran bagi guru dan kepala sekolah adalah dengan mengadakan pelatihan terkait dengan hambatan belajar matematika serta meningkatkan kualitas mengajar.